Estimasi Kelayakan Penambangan Bijih Timah Blok Kemingking, Desa Kemingking, Kecamatan Sungai Selan PT Mitra Stania Prima: Tin Ore Mining Feasibility Estimation Block Kemingking, Kemingking Village, District Sungai Selan PT Mitra Stania Prima - Daryono, Yuli; Mardiah, Mardiah; Pitulima, Janiar (Program Studi Teknik Pertambangan Universitas Bangka Belitung, 2016)
The mining industry is in need of a good planning so that the planned production targets can beachieved at minimum cost and revenue optimally, and can generate cash flow that will maximizerevenue each year over the life of the mine took place. Tin ore mining economic studies based onthe technical design data, so that the determination of the cost will be considered by the company.Components of the economic study of tin ore mining in terms of costing, revenue from the sale ofproducts, the calculation of cash flow, net present value, internal rate of return, payback period,sensitive analysis. Based on the results of studies on tin ore mine PT Mitra Stania Prima BlockKemingking acquired total reserves of tin ore amounted to 2.801,531 tons, by applying the method ofmining Open Pit Mining. From the economic feasibility calculations assuming the bank rate of 12%was obtained net present value of Rp 11.810.941.184.00, internal rate of return of 19.04%, and apayback period of 4.78 months for 2 years. Based on these results the project of PT Mitra StaniaPrima Block Kemingking feasible to continue.